A new global burned area product for climate assessment of fire impacts. Issue 5 (17th March 2016) - Chuvieco, Emilio; Yue, Chao; Heil, Angelika; Mouillot, Florent; Alonso‐Canas, Itziar; Padilla, Marc; Pereira, Jose Miguel; Oom, Duarte; Tansey, Kevin
Abstract: Aim This paper presents a new global burned area (BA) product developed within the framework of the European Space Agency's Climate Change Initiative (CCI) programme, along with a first assessment of its potentials for atmospheric and carbon cycle modelling. Innovation Methods are presented for generating a new global BA product, along with a comparison with existing BA products, in terms of BA extension, fire size and shapes and emissions derived from biomass burnings. Main conclusions Three years of the global BA product were produced, accounting for a total BA of between 360 and 380 Mha year −1 . General omission and commission errors for BA were 0.76 and 0.64, but they decreased to 0.51 and 0.52, respectively, for sites with more than 10% BA. Intercomparison with other existing BA datasets found similar spatial and temporal trends, mainly with the BA included in the Global Fire Emissions Database (GFED4), although regional differences were found (particularly in the 2006 fires of eastern Europe). The simulated carbon emissions from biomass burning averaged 2.1 Pg C year −1 .